2021
DOI: 10.3390/pathogens10121547
|View full text |Cite
|
Sign up to set email alerts
|

Bovine Brucellosis in Gauteng, South Africa: Seroprevalence amongst Cattle Handlers and Variables Associated with Seropositive Cattle Herds, 2014–2016

Abstract: In South Africa, the prevalence of cattle handler exposure to Brucella on cattle farms is unknown and risk factors and cattle symptoms associated with infected cattle herds are unavailable. To address this gap, a case-control study of cattle herds was conducted in Gauteng province and farm workers and veterinary officials were tested for exposure to Brucella. Seroprevalence amongst farm workers exposed to case herds ranged from 4.0% (BrucellaCapt®) to 16.7% (IgG ELISA®), compared to those exposed to control he… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 55 publications
0
1
0
Order By: Relevance
“…The associated risk to workers to brucellosis will be influenced by the brucellosis infection in livestock with which the workers have had contact. This is reflected by the low to moderate brucellosis seroprevalence (4.0% (BrucellaCapt) to 16.7% (IgG ELISA)) of farm workers on brucellosis infected farms compared to low seroprevalence [1.9% (BrucellaCapt ® ) to 5.7% (IgG ELISA ® )] on farms free of brucellosis in South Africa (27). In South Africa, we have limited data on the brucellosis prevalence in animals.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The associated risk to workers to brucellosis will be influenced by the brucellosis infection in livestock with which the workers have had contact. This is reflected by the low to moderate brucellosis seroprevalence (4.0% (BrucellaCapt) to 16.7% (IgG ELISA)) of farm workers on brucellosis infected farms compared to low seroprevalence [1.9% (BrucellaCapt ® ) to 5.7% (IgG ELISA ® )] on farms free of brucellosis in South Africa (27). In South Africa, we have limited data on the brucellosis prevalence in animals.…”
Section: Discussionmentioning
confidence: 99%
“…These studies were conducted in various countries/regions, each with its unique zoonotic disease profile in abattoir facilities that determine the risk factors identified in each study. In South Africa the only published record focusing on occupational workers exposed to brucellosis is the seroprevalence amongst farm workers exposed to brucellosis case farms that are higher, ranging from 4.0% (BrucellaCapt ® ) to 16.7% (IgG ELISA ® ), compared to those exposed to brucellosis negative control farms where seroprevalence ranged from 1.9% (BrucellaCapt ® ) to 5.7% (IgG ELISA ® ) (27). There are no empirical data or published reports on brucellosis seroprevalence and risk factors in abattoir workers in South Africa.…”
Section: Introductionmentioning
confidence: 99%
“…Limited studies have reported BB’s prevalence or incidence rate in South Africa cattle populations. Previous findings have reported on the seroprevalence of BB in Gauteng, Mpumalanga (Mnisi area), and KwaZulu Natal and determined seroprevalence of 2.33, 0.88, and 1.3%, respectively, with the latter two focusing on communal cattle in municipal dip tanks ( Matekwe, 2011 ; Chisi et al, 2014 ; Govindasamy et al, 2021 ). Moreover, introducing compulsory calf vaccinations in South Africa has considerably decreased the overall BB prevalence from approximately 10.5% in 1976 to 1.4% in 1988 ( Godfroid et al, 2004 ).…”
Section: Discussionmentioning
confidence: 99%
“…Te diagnostic performance characteristics of ELISAs and FPA are comparable with or better than that of the CFT, and as they are technically simpler to perform and more robust, their use may be preferred [10]. Te problem with SA partial brucellosis scheme focusing only on bovines is once the disease has been established in a herd, it is difcult to control as it has variable incubation periods ranging from several months to at least two years and even nine years as reported [15]. Tese problems make control and elimination from herds costly and difcult as it takes a minimum of two years after removal of infected animals to declare a herd free and decades to declare countries free of brucellosis [15].…”
Section: Introductionmentioning
confidence: 99%
“…Te problem with SA partial brucellosis scheme focusing only on bovines is once the disease has been established in a herd, it is difcult to control as it has variable incubation periods ranging from several months to at least two years and even nine years as reported [15]. Tese problems make control and elimination from herds costly and difcult as it takes a minimum of two years after removal of infected animals to declare a herd free and decades to declare countries free of brucellosis [15]. As human brucellosis is mainly caused by contact with Brucellainfected animals that could be asymptomatic [16], their secretions and carcasses result in occupational public health risks for those workers in contact with animals such as abattoir workers, animal handlers, and veterinarians.…”
Section: Introductionmentioning
confidence: 99%